Chaotic cipher using the duffing equation - Roda, Fernando (2010)
We propose a plain files cipher by means of a stream cryptosystem scheme with chaotic addition and a symmetric key. The sequence of numbers used for encryption is generated by a continuous chaotic dynamical system; in particular, we choose the forced Duffing equation since this kind of systems is sensitive to the initial conditions. In a chaotic system, the answer can became periodic during the process of numeric integration. We introduce an heuristic method to break this periodicity.